2001
DOI: 10.1002/1521-3773(20010302)40:5<944::aid-anie944>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Membrane Photolabeling of the Transmembrane Domain of Glycophorin A in Phospholipid Vesicles

Abstract: The tandem use of the photosensitive bola‐amphiphile 1 (X=3H) and cholesterol enabled the determination of the center of the transmembrane domain of glycophorin A (131 amino acid residues) in a membrane by selective functionalization of the protein within a phospholipid bilayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They observed that most of the cross-linking involved the carboxyl group of Glu 70 , thus suggesting that this residue was located within the bilayer . However, 20 years later the Nakatani group used the same approach with a different lipid probe and obtained very different results. , They used a benzophenone-based bola-phospholipid probe ( 10 , Figure ), thus guaranteeing that the label was located at the center of the bilayer, with no possibility for looping back. DSC characterization of the probe 10 showed complete miscibility with DMPC in the fluid phase .…”
Section: Photolabeling Using Photoreactive Lipidsmentioning
confidence: 99%
“…They observed that most of the cross-linking involved the carboxyl group of Glu 70 , thus suggesting that this residue was located within the bilayer . However, 20 years later the Nakatani group used the same approach with a different lipid probe and obtained very different results. , They used a benzophenone-based bola-phospholipid probe ( 10 , Figure ), thus guaranteeing that the label was located at the center of the bilayer, with no possibility for looping back. DSC characterization of the probe 10 showed complete miscibility with DMPC in the fluid phase .…”
Section: Photolabeling Using Photoreactive Lipidsmentioning
confidence: 99%